2020
DOI: 10.1038/s41598-020-75267-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between plasma levels of homocysteine, folate, and vitamin B12, and dietary folate intake and hypertension in a cross-sectional study

Abstract: There are few studies examining the association between homocysteine (Hcy) level and the risk of hypertension with consideration for folate and vitamin B12 as related to Hcy level. We simultaneously examined the associations of plasma levels of Hcy, folate, and vitamin B12, and dietary folate intake with the prevalence of hypertension. Participants included 1046 men and 1033 women (mean age ± standard deviation: 56.0 ± 8.9 years) in the Japan Multi-Institutional Collaborative Cohort Study. Dietary folate intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Similarly, it is speculated that adequate levels of folate in the blood may lower risks of hypertension by lowering the homocysteine levels. Hyperhomocysteinemia is responsible for hypertension by increasing oxidative stress [ 42 45 ]. Increased homocysteine in plasma causes oxidative stress and endothelial dysfunction, leading to vasoconstriction, vasodilation by nitric acid, and nitrate reduction, all of which increase blood pressure [ 42 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, it is speculated that adequate levels of folate in the blood may lower risks of hypertension by lowering the homocysteine levels. Hyperhomocysteinemia is responsible for hypertension by increasing oxidative stress [ 42 45 ]. Increased homocysteine in plasma causes oxidative stress and endothelial dysfunction, leading to vasoconstriction, vasodilation by nitric acid, and nitrate reduction, all of which increase blood pressure [ 42 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperhomocysteinemia is responsible for hypertension by increasing oxidative stress [ 42 45 ]. Increased homocysteine in plasma causes oxidative stress and endothelial dysfunction, leading to vasoconstriction, vasodilation by nitric acid, and nitrate reduction, all of which increase blood pressure [ 42 , 44 ]. A high homocysteine level, also called hyperhomocysteinemia, is known to be regulated through the intake of grain fortification foods containing folate [ 46 ] and folic acid supplements [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cohort study published by Tumura et al, on postmenopausal women from Japan found that no correlation between depressive symptoms and vitamin B12 level (30). A cross-sectional study published by Ao et al, on the elderly population from Japan found that there was no significant association between serum folate concentration and gait speed nor between serum B12 and physical performance among women.…”
Section: Vitamin B and Physical Healthmentioning
confidence: 97%
“…The parameters mainly used for these studies were HCY, folate and vitamin B12. Both decreased vitamin B12 and elevated HCY positively associated and linked with hypertension (30). According to Misora Ao et al (31) the serum folate levels contribute to the handgrip and limb muscle strength.…”
Section: B Vitamin Status and Its Impact On Physical Healthmentioning
confidence: 98%